2015
DOI: 10.4293/jsls.2014.00246
|View full text |Cite
|
Sign up to set email alerts
|

Distal Pancreatectomy and Splenectomy: A Robotic or LESS Approach

Abstract: Introduction:The role and application of robotic surgery are debated, particularly given the expansion of laparoscopy, especially laparoendoscopic single-site (LESS) surgery. This cohort study was undertaken to delineate differences in outcomes between LESS and robotic distal pancreatectomy and splenectomy.Methods:With Institutional Review Board approval, patients undergoing LESS or robotic distal pancreatectomy and splenectomy from September 1, 2012, through December 31, 2014, were prospectively observed, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 22 publications
4
40
2
1
Order By: Relevance
“…[50][51][52] However, there was no significant difference in intraoperative blood loss, conversion to open surgery, spleen preserving, postoperative complications, and length of postoperative hospital stay between the two groups. [50][51][52][53][54][55] For malignant tumors, the rates of negative surgical margins and the number of lymph nodes harvested were higher in R-LDP. 54 However, some other studies reported that there were no significant differences between the two groups.…”
Section: Robotic Laparoscopic Distal Pancreatectomymentioning
confidence: 49%
“…[50][51][52] However, there was no significant difference in intraoperative blood loss, conversion to open surgery, spleen preserving, postoperative complications, and length of postoperative hospital stay between the two groups. [50][51][52][53][54][55] For malignant tumors, the rates of negative surgical margins and the number of lymph nodes harvested were higher in R-LDP. 54 However, some other studies reported that there were no significant differences between the two groups.…”
Section: Robotic Laparoscopic Distal Pancreatectomymentioning
confidence: 49%
“…Supine [2, 32, 34, 36, 38, 39], right lateral [35], and semilateral [33, 37] positions with [2, 32, 34, 38, 39] or without legs apart have been described, while reverse Trendelenburg after establishing the pneumoperitoneum was used by all groups. The surgical technique described is similar among the reports with minor modifications.…”
Section: Resultsmentioning
confidence: 99%
“…К концу 2015 г. в мировой литературе было опубликовано 426 слу-чаев выполнения этой операции [13][14][15][16][17][18]. Показаниями к операции послужили нейроэндокринная опухоль (29%), протоковая аденокарцинома (23,9%), серозная или муци-нозная цистаденома (22,6%), внутрипротоковая папилляр-но-муцинозная опухоль (20%), другие заболевания (4,5%) [19][20][21][22].…”
Section: Discussionunclassified